An open source IEC 61131-3 integrated development environment - Mário de Sousa (2007)
The IEC 61131-3 standard defines a commonframework for programming PLCs (Programmable LogicControllers), which includes the complete definition of fourprogramming languages and a state machine definitionlanguage. Industrial PLC vendors are slowly offering supportfor this standard, however small inconsistencies remainbetween their implementations, transferring programsbetween vendors is almost impossible due to different fileformats, and licenses are generally too expensive to allowstudents do install these commercial solutions on their owncomputers.To this end, the authors have developed an IntegratedDevelopment Environment (IDE) for the IEC 61131-3framework, which is being offered to the general public underthe GNU Public License (GPL). The IDE consists of aGraphical User Interface (GUI) and a backend compiler.Using the GUI the user may develop programs in any of thefour programming languages, as well as the state machinedefinition language. The backend compiler is used to convertthese programs into equivalent C++ programs which maylater be compiled and executed on various platforms.